Business Development Menggunakan Model Bisnis Canva - Sofyan Mufti Prasetiyo; Dimyati; Angga Syaf Putra; Abdul Aziz (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
In developing a business, it is necessary to implement a business model known as the Business Model Canvas. In this business model, the company tells about the company's internal and external conditions. The company's business model canvas displays a block/business element model consisting of nine elements. This approach is used to apply the implementation of the Business Model Canvas in the UKM "Abi Jaya Makmur". This study aims to evaluate the business model of shredded products using Business Model Canvas analysis. The data obtained in this study were the results of interviews with questionnaires to the owner, two employees and consumers of the catfish pecel business as many as 30 people in the city of Depok and the results of supporting literature studies. The results obtained from this study are that each identified element has been refined using a SWOT analysis. From this analysis it is known that improvements are needed in almost all elements of the business model in the Abi Jaya Makmur pecel lele business. The improvement of the Abi Jaya Makmur Pecel Lele business model is a sustainable focus on improving marketing activities. Mainly through online media to increase revenue